Skeletal age assessed by Greulich-Pyle: Intra-observer and inter-observer agreement among male pubertal tennis players. - Jorge M Celis-Moreno; Diogo V Martinho; Manuel J Coelho-E-Silva; Isabel Fragoso; Luís P Ribeiro; Élvio R Gouveia; Tomas Oliveira; João Gonçalves-Santos; Oscar M Tavares; Ricardo R Cayolla; Pedro Duarte-Mendes; Jan M Konarski; et al. (PLoS ONE)
The assessment of biological maturation is a central topic in pediatric exercise sciences. Skeletal age (SA) reflects changes in each bone of the hand and wrist from initial ossification to the adult state. This study examined intra-observer and inter-examiner agreement is Greulich-Pyle (GP) assessments of SA in 97 male tennis players 8.6-16.8 years of age. Two observers independently examined all films on two occasions using the GP method. The SA of each bone was evaluated. The mean and median of SAs assigned for each bone was the individual SA for each participant. The calculation was exclusively based on the bones that were not skeletally mature. Intra-observer mean differences were significant for several bones with better results by the experienced examiner (observer B). Comparisons between SA values of the two independent observers indicated significant differences for the ulna, metacarpals II and III, and distal phalanx V. Nevertheless, the magnitude of the bone-specific differences was small, perhaps trivial. Differences in individual SA values of the tennis players based on the non-mature bones of the hand-wrist were negligible based on the mean (0.04±0.39, t = 0.321, p = 0.749) or the median (0.05±0.58, t = 0.007, p = 0.994). Nevertheless, the current study confirmed examiners as a source of error in the estimation of SA using the Greulich-Pyle method and highlighted the importance of calculating SAs based on non-mature bones among adolescent players.